Meningkatkan Efisiensi Perdagangan: Sinergi Berkelanjutan Indonesia-Uni Eropa Melalui ARISE+ Indonesia Trade Support Facility - Heriamsal, Krisman (Global and Policy Journal of International Relations, 2024)
ABSTRACT This study aims to analyze the impact of the European Union's support initiative for Indonesia's trade facilitation through the ASEAN Regional Integration Support from European Union plus Indonesia (ARISE+ Indonesia) program on trade relations between the European Union and Indonesia. This research uses a qualitative approach, and uses data collection techniques through literature studies, by studying, analyzing, and reviewing literature sourced from books, e-books, journals, documents, and online media. By using the theory of liberalism, the results of this study show that the ARISE+ Indonesia program has succeeded in increasing trade flows between the European Union and Indonesia, improving the quality of Indonesian export products, creating open access for Indonesian export products to enter the global market, and increasing the promotion and productivity of Indonesian geographical indication products. Keywords: European Union, ARISE+ Indonesia, Trade Facilitation ABSTRAK Penelitian ini bertujuan untuk menganalisis dampak dari inisiatif dukungan Uni Eropa untuk fasilitasi perdagangan Indonesia melalui program ASEAN Regional Integration Support from European Union plus Indonesia (ARISE+Indonesia) terhadap hubungan perdagangan kedua pihak. Penelitian ini menggunakan pendekatan kualitatif, dan menggunakan teknik pengumpulan data melalui studi pustaka, dengan cara mempelajari, menganalisis, dan menelaah literatur yang bersumber dari Buku, E-book, Jurnal, dokumen, dan media daring. Dengan menggunakan teori liberalisme, Hasil penelitian ini menunjukkan bahwa program ARISE+ Indonesia telah berhasil meningkatkan arus perdagangan antara Uni Eropa dan Indonesia, meningkatkan kualitas produk ekspor Indonesia, menciptakan keterbukaan akses bagi produk ekspor Indonesia untuk memasuki pasar global, serta meningkatkan promosi dan produktivitas produk indikasi geografis Indonesia. Kata Kunci: Uni Eropa, ARISE+ Indonesia, Fasilitasi Perdagangan